A New Approach to Street Lighting Design. Issue 3 (2nd July 2016) - Sędziwy, Adam
ABSTRACT: This article compares two methods of roadway lighting design for situations compliant with EN 13201-2 ME/MEW series. The goal is to find out which one yields a more energy-efficient installation. The first method (further referred to as the "default" one), used by industry-standard software, assumes equally spaced luminaires (in any arrangement) and uniform width of the corresponding roadway. The second one (referred to as the "custom" one) operates on exact inventory data including spacing, road width, mounting height, and other parameters given per luminaire rather than set up globally. Both approaches are assumed to find solutions (installation setups) giving minimal energy consumption, which is accomplished, among others, by lamp dimming. The article presents the performed computations, discusses the obtained results, and analyzes the factors that might influence them. Results show that using the custom computation method and actual inventory data may bring an energy usage reduction at the level of 10% and more, compared to the default approach. Another issue critical from the practical point of view is the complexity of the solution-finding process. Although commonly known programs allow for building custom (nonuniform) scenes, the trial-and-error method of solution finding remarkably increases the design preparation time. Special heuristics embedded in the custom method allow avoiding the complexity issue and enable bulk processing, which is crucial in the case of large-scale computations made, for example, for large retrofits.